PENDIDIKAN KESEHATAN PENDAMPINGAN LANSIA UNTUK PENANGANAN KEJADIAN JATUH - Sri Legawati; R Sri Rezeki; Efi Irwansyah Pane; Sri Julita; Muhammad Arif Mangunsong; Dahlia Sapuri (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
Falls in the elderly are a leading cause of serious injury, which can significantly impact quality of life. Therefore, health education regarding emergency measures is crucial to improve the preparedness of the elderly and their surrounding communities in dealing with such situations. Given the high rate of falls in the elderly, various studies indicate that approximately one-quarter to one-third of elderly people in the community experience at least one fall per year, and this figure can exceed one-third in the very elderly, making falls a significant public health issue. This community service activity aimed to provide basic understanding and skills regarding fall management in the elderly through an interactive lecture. Fifty elderly participants participated in the activity and a three-person implementation team with clearly defined roles. Evaluation results indicated an increase in participants' understanding of appropriate emergency steps after a fall, as well as the creation of effective communication between participants and the presenters. This activity had a positive impact in increasing awareness and knowledge of the elderly regarding the importance of prompt and appropriate fall management. Continuing health education and practical training are recommended as follow-up measures to strengthen the capacity of the elderly to respond to emergencies.